Outcomes of patients with severe sepsis after the first 6 hours of resuscitation at a regional referral hospital in Uganda - Amir, Abdallah; Saulters, Kacie J.; Olum, Sam; Pitts, Kelly; Parsons, Andrew; Churchill, Cristina; Taseera, Kabanda; Muhindo, Rose; Moore, Christopher C. (Journal of Critical Care, 2016)
Introduction: The optimal resuscitation strategy for patients with severe sepsis in resource-limited settings is unknown. Therefore, we determined the association between intravenous fluids, changes in vital signs and lactate after the first 6 hours of resuscitation from severe sepsis, and in-hospital mortality at a hospital in Uganda. Materials and methods: We enrolled patients admitted with severe sepsis to Mbarara Regional Referral Hospital and obtained vital signs and point-of-care blood lactate concentration at admission and after 6 hours of resuscitation. We used logistic regression to determine predictors of in-hospital mortality. Results: We enrolled 218 patients and had 6 hour postresuscitation data for 202 patients. The median (interquartile range) age was 35 (26-50) years, 49% of patients were female, and 57% were HIV infected. The in-hospital mortality was 32% and was associated with admission Glasgow Coma Score (adjusted odds ratio [aOR], 0.749; 95% confidence interval [CI], 0.642-0.875; P b .001), mid-upper arm circumference (aOR, 0.876; 95% CI, 0.797- 0.964; P = .007), and 6-hour systolic blood pressure (aOR, 0.979; 95% CI, 0.963-0.995; P = .009) but not lactate clearance of 10% or greater (aOR, 1.2; 95% CI, 0.46-3.10; P = .73). Conclusions: In patients with severe sepsis in Uganda, obtundation and wasting were more closely associated with in-hospital mortality than lactate clearance of 10% or greater.
Keywords: Severe sepsis; Resuscitation; Monitoring; Mortality; Uganda; Africa